Implementation of Merdeka Belajar in the Perspective of Islamic Education at SMK NU Mekanika Buntet Pesantren Cirebon - Fahad Achmad Sadat (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The Freedom of learning Policy issued by the Minister of Education and Culture (Mendikbud) Nadiem Makarim on November 22, 2019 changed many things in the national education process. Starting from learning practices that place more emphasis on student interests, the assessment process that no longer focuses on cognitive abilities and is handed over to the head of the education unit, to the process of preparing the Lesson Plan (RPP) which is simpler.In the world of Islamic education, this concept is not new. Since classical times, education in Islam has emphasized independence. However, the concept is not institutionalized. Therefore, when the Minister of Education and Culture Nadiem Makarim issued this policy, it seemed as if it was a new thing. NU Mekanika a Islamic Vocational School is preparing to apply the concept of Independent Learning. However, its implementation is not optimal. There are two obstacles. First, because this policy is still new, schools still need examples or comparative studies with other schools that have implemented this policy first. Second, the Covid-19 pandemic, which has lasted for almost 2 years, has made the teaching and learning process more carried out online